Pluteus anatolicus (Pluteaceae, Agaricales): a new species of Pluteus sect. Celluloderma from Turkey based on both morphological and molecular evidence - Kaygusuz, Oguzhan; Knudsen, Henning; Menolli Jr., Nelson; Türkekul, Ibrahim (Phytotaxa, 2021)
A new species belonging to Pluteus sect. Celluloderma with specimens collected in Artvin Province, Black Sea region, northeastern Turkey, is described as Pluteus anatolicus sp. nov. based on morphological characteristics and molecular data (nrITS). The new species was found in Fagus orientalis forests and is mainly characterized by a terrestrial habit, small-sized basidiomata, cracking pileus surface depressed at the center, broadly ellipsoid to ellipsoid basidiospores, narrowly utriform to narrowly fusiform or fusiform pleurocystidia with obtuse or subcapitate apex and sometimes with elongated pedicel, narrowly clavate to clavate cheilocystidia, absence of caulocystidia and pileipellis elements predominantly with a broadly mucronate apex and long pedicel. A comprehensive description and illustrations are provided, with its phylogenetic placement based on ITS also evaluated and including comparison to morphologically similar taxa and phylogenetically related species.